ANALISIS HUBUNGAN ANTARA PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN BIAYA AUDIT DENGAN LAPORAN KEUANGAN XBRL SEBAGAI VARIABEL MODERASI (Studi pada Perusahaan Sektor Manufaktur yang Terdaftar Pada BEI Tahun 2017-2019) - Khoirul Alfisyahrin; Karlina Aprilia Kusumadewi (Diponegoro Journal of Accounting, 2022)
The purpose of this study is to examine the relationship of corporate social responsibility (CSR) on audit fee and the impact of XBRL based financial report on the association between corporate social responsibility (CSR) and audit fee. The dependent variable that used in this study is audit fee. Corporate social responsibility (CSR) used as independent variable. Furthermore, this study used XBRL based financial report as a moderating variable.The sample in this study consists of 137 manufacture companies that listed on Indonesia Stock Exchange in the period 2017-2019. The data that used in this study was secondary data and selected by using purposive sampling method. The technique of analysis used for examining the hypothesis was multiple regression analysis.Based on the empirical results of this study show that corporate social responsibility (CSR) has positive significant influence on Audit Fee but this study did not find the association of  XBRL based financial report between corporate social responsibility (CSR) and audit fee.